Food and Shelter Standards in Humanitarian Action - POTHIAWALA, Sohil (Turk J Emerg Med, 2016)
The number of disasters, both natural as well as man-made, has been increasing in frequency in the recent years. This leads to short as well as long-term effects on food security and shelter, requiring humanitarian assistance. This article aims to identify the principles and standards that are applicable to food and shelter related aid that needs to be provided by the co-operation of the local government as well as the relevant supporting organizations. Also, food and shelter security during a disaster response is achieved through better preparedness. The level of preparedness must include risk assessment, contingency planning, stockpiling of equipment and supplies, emergency services and stand-by arrangements, communications, information management and coordination arrangements between various agencies involved. Discussing these issues would contribute to a better understanding of the implications of the right to adequate food and shelter, which in complex humanitarian emergencies, is one of the key necessities of the affected population.